Growth Characteristics of Rhizophagus clarus Strains and Their Effects on the Growth of Host Plants - Lee, Eun-Hwa (Mycobiology, 2015)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous in the rhizosphere and form symbiotic relationships with most terrestrial plant roots. In this study, four strains of Rhizophagus clarus were cultured and variations in their growth characteristics owing to functional diversity and resultant effects on host plant were investigated. Growth characteristics of the studied R. clarus strains varied significantly, suggesting that AMF retain high genetic variability at the intraspecies level despite asexual lineage. Furthermore, host plant growth response to the R. clarus strains showed that genetic variability in AMF could cause significant differences in the growth of the host plant, which prefers particular genetic types of fungal strains. These results suggest that the intraspecific genetic diversity of AMF could be result of similar selective pressure and may be expressed at a functional level.